Squirrel Monkeys Support Replication of BK Virus More Efficiently than Simian Virus 40: an Animal Model for Human BK Virus Infection - Zaragoza, Concepcion (American Society for Microbiology, 2005)
We performed experiments to test the suitability of squirrel monkeys (Saimiri sciureus) as an experimental model for BK virus (BKV) and simian virus 40 (SV40) infection. Four squirrel monkeys received intravenous inoculation with BKV Gardner strain, and six squirrel monkeys received intravenous inoculation with SV40 777 strain. Eight of 10 monkeys received immunosuppression therapy, namely, cyclophosphamide subcutaneously either before or both before and after viral inoculation. The presence of viral infection was assessed by quantitative real-time PCR amplification of viral DNA from blood, urine, and 10 tissues. We found that squirrel monkeys were susceptible to infection with BKV, with high viral copy number detected in blood and viral genome detected in all tissues examined. BKV genome was detected in urine from only one monkey, while three monkeys manifested focal interstitial nephritis. BKV T antigen was expressed in renal peritubular capillary endothelial cells. By contrast, SV40 was detected at very low copy numbers in only a few tissues and was not detected in blood. We conclude that the squirrel monkey is a suitable animal for studies of experimental BKV infection and may facilitate studies of viral entry, pathogenesis, and therapy.